Pemberdayaan Penyandang Disabilitas Pada Program PermataBRAVE Corporate Social Responsibility (CSR) PT Bank Permata Tbk - Wahyudi, Ayuananda; Nurwulan, Riany Laila (Jurnal Publisitas, 2025)
The right to accessibility in obtaining employment is one of the major challenges faced by persons with disabilities. Many of them are unable to secure jobs due to low educational backgrounds and a lack of skills. Through empowerment initiatives under Corporate Social Responsibility (CSR) programs in companies, persons with disabilities can fulfill their daily needs by becoming employees in these companies. One such company with a CSR program aimed at people with disabilities is Permata Bank. Based on this background, the researcher conducted a study on Corporate Social Responsibility (CSR) with the theme: "Empowerment of Persons with Disabilities through the PermataBRAVE CSR Program at PT Bank Permata Tbk." The purpose of this research is to analyze the outcomes of the empowerment of persons with disabilities through the PermataBRAVE CSR program at PT Bank Permata Tbk. The research method used is a qualitative descriptive approach with purposive sampling as the technique for selecting informants. Data collection techniques included in-depth interviews, observation, and documentation. The research findings are analyzed based on three pillars of empowerment: 1) Education, 2) Empowerment, and 3) Enhancement (Provision of Assistive Tools). The findings indicate that the empowerment of persons with disabilities in the PermataBRAVE program includes:(1) Gaining knowledge — the program emphasizes financial management and the use of the internet in today’s digital era. (2) Gaining skills — helping individuals with disabilities to secure employment, build self-confidence, and prove to society that they possess capabilities and skills equal to others. (3) Gaining power — participants undergo a one-month program after which they are given the opportunity to work at PermataBank for six months across various divisions. This serves as a means to provide work experience and further develop their skills.